2013
DOI: 10.1007/s00256-013-1618-3
|View full text |Cite
|
Sign up to set email alerts
|

MRI features most often associated with surgically proven tears of the spring ligament complex

Abstract: The complex orientation of the medio-plantar ligament makes its evaluation unreliable due to the difficulty obtaining diagnostic quality imaging and our inability to correlate MRI findings in this portion of the ligament with surgically proven injury. However, MRI abnormalities of the superior-medial ligament are consistent, reproducible, and correlate with surgical pathology. As our incomplete understanding of the flexible flatfoot deformity evolves, our ability to recognize injury to the spring ligament may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In addition, associated pathologies such as spring ligament (Yao et al 1999; Williams et al 2013) and sinus tarsi abnormalities are seen on MRI especially in advanced PTT dysfunction and could then be addressed during surgery (Balen and Helms 2001; Shibuya et al 2008). For these indications, the use of MRI partially competes with other imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, associated pathologies such as spring ligament (Yao et al 1999; Williams et al 2013) and sinus tarsi abnormalities are seen on MRI especially in advanced PTT dysfunction and could then be addressed during surgery (Balen and Helms 2001; Shibuya et al 2008). For these indications, the use of MRI partially competes with other imaging modalities.…”
Section: Discussionmentioning
confidence: 99%
“…4 Compromise of the SL has been implicated as a primary causative factor in peritalar subluxation. 6,16 Therefore surgical repair or reconstruction of the ligament has become an important adjunct to treating posterior tibial tendon abnormalities. [17][18][19][20] This requires extensive soft-tissue dissection because the ligament is a deep structure.…”
Section: Discussionmentioning
confidence: 99%
“…The fibrocartilaginous articular surface and integrity of the SL can be examined from its calcaneal insertion to its navicular insertion (Fig 4, Video 1). 6,8 If a tear of the SL is confirmed, the ligament can be exposed and repair performed either in an open manner or arthroscopically.…”
Section: Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Limited literature exists regarding the MRI appearance of spring ligament tears. [27][28][29][30] In 1999 Yao et al reported 13 surgically proven cases of rupture or laxity of the spring ligament complex, a moderate sensitivity (55-77%) but a high specificity (100%) of MR imaging. 27 The best criteria of an insufficient spring ligament was thickening of >6 mm and signal heterogeneity of the smCNL best depicted on proton-weighted images.…”
Section: Mr Findings Of Spring Ligament Complex Injuriesmentioning
confidence: 99%